Atypical Presentation of Marginal Zone Lymphoma as Isolated Diffuse Bone Marrow Involvement: Utility of F-18 FDG PET/CT in Diagnosis and Response Assessment - Gauthaman, Dinesh Kumar; Subramanyam, Padma; Palaniswamy, Shanmuga Sundaram (World Journal of Nuclear Medicine, 2022)
Non-Hodgkin's lymphoma (NHL) with secondary bone marrow involvement is relatively common. However, isolated involvement of bone marrow in marginal zone type of NHL is atypical and rare. Here, we describe a patient of atypical marginal zone lymphoma with isolated bone marrow involvement who presented with weight loss and bicytopenia, where F-18 FDG PET/CT (fluorine-18-labeled fluorodeoxyglucose positron emission tomography with computed tomography) imaging played a pivotal role in establishing the diagnosis when conventional imaging modalities were unremarkable. The patient was successfully treated with systemic chemotherapy (rituximab, cyclophosphamide, prednisolone) and achieved complete remission, as demonstrated by a follow-up F-18 FDG PET/CT scan.
Keywords: marginal zone lymphoma; F-18 FDG PET/CT; isolated bone marrow involvement; atypical presentation; case report